The Introduction of 3D applications Animal In Indonesia Using Augmented Reality Marker-Based Tracking Method - Bagas Syihabudin (Institute of Computer Science (IOCS), 2018)
In this study, specifically about endangered animals can be done with a variety of media and for users aged 5 to 10 and must be accompanied by parents. This research Utilizes the benefits of marker-based tracking methods to familiarize endangered animals in 3D on sponsored smartphone devices. Augmented Reality Also has a FAST Angle Detection algorithm to support a marker object in it. In the results and testing of 300 angles produce 18.75% of objects Obtained, 81.25% of the objects are not supported, for an angle of 600 produces 27.08% of objects received overall, 54.17% of objects received mostly, 18.75% the object is not liked and the angle of 900 produces 58.4% of the objects taken as a whole, 33.3% of the most objects Obtained, 8.